Consejería psicoeducacional y la salud mental en los estudiantes de la Escuela de Educación Básica Manuel de Jesús Calle - Sandoya Fuentes, Silvia Tamara (2019)
The progressive development of children and adolescents absorbs the influence of aspects between which the environment, parents and technology are located, so that, during childhood, social and interactive development gathers a great influence of technological means, specifically of the excessive use of the mobile phone so that adolescents' mental health can be exposed to disruptive situations. The present study sought to promote psychoeducational counseling as the primary sustenance of the mental health of the students of the Manuel de Jesús Calle School of Basic Education. Through interviews with students, parents and teachers will be recognized the benefits of counseling in the various behaviors of students, as well as stimulate skills to interact in the social environment, adaptability to the environment and improvements in academic performance in the different contexts. The purpose of the work was to expand knowledge about psychoeducation, to have scientific evidence to support the political decisions for the design and implementation of the proposal on Psychoeducational Counseling Workshops that favor the mental health of students and that is converted into positive changes in the mental health of students and their families. In addition, a case study was proposed with qualitative methodology of exploratory-descriptive type, so data collection was carried out through participant observations, surveys of students, teachers and parents and notes of field work It was executed in the same facilities of the educational institution.